Covid-19 Prevention Handling Model Bali Province Government - I Ketut Sukadana; I Nyoman Sutama; Ni Made Sukaryati Karma (Sociological Jurisprudence Journal, 2022)
According to data from the Indonesian Covid Task Force, as of Augustus 2, 2021, there were 3,462,800 cases and 97,291 deaths. Even though in terms of the quantity of Balinese people affected by COVID-19, which is around 2,3% of the sufferers nationally (2,231 deaths), the social impact it causes is very broad, especially in the tourism sector which is almost totally not operating. The government has taken policies or steps to overcome the impact of the Covid-19 pandemic. All parties are also expected to be able to make efforts to prevent transmission and mitigate the impact that occurs, from the Government, Provincial Government, Regency / City Government, and all levels of society. Efforts to improve the health status of the highest in the form of efforts to prevent disease transmission by involving the community at large. Interesting legal issues to study are as follows: Policies implemented by the Bali Provincial Government in Preventing the Transmission of Covid-19. This study aims to obtain and examine the model applied by the Bali Provincial Government in handling the spread of COVID-19. The results of the study show The policies carried out by the Provincial Government of Bali in the Prevention of Covid-19 Transmission are to realize the acceleration of handling health related to COVID-19, to realize the acceleration of handling the impact of COVID-19 on the economy, and to realize the acceleration of handling the impact of COVID-19 on the community, in the form of a Social Safety Net. The scope of the policy includes: budget reallocation, handling health related to COVID-19, handling the impact of COVID-19 on the economy, and handling the impact of COVID-19 on the community in the form of a Social Safety Net. Handling the Prevention of Covid-19 Transmission is by forming a Task Force based on Traditional Villages and handling health by the Provincial Task Force. The involvement of the traditional village at the behest of the ruler means not respecting the traditional village as an institution that has genuine autonomy that cannot be governed by parties outside the traditional village. Conditions would be different if the initiative to assist the implementation of the handling of Covid-19 came from the traditional village itself.